ELECTRIC FIELD INDUCED CLUSTERING IN SUSPENSION OF E.COLI BACTERIA (FUDMA JOURNAL OF SCIENCES, 2020)
Living microswimmers such as bacteria tend to collective organize into communities in response to external field. As this microswimmers swims, it stirs the fluid and creates flows which generally lead to hydrodynamic interactions with its neighbors. The flows can sometimes affect the collective dynamics of the suspension leading to complex cell interactions. To further understand the role of fluid flow in the dynamics of bacterial suspension, we applied electric field to a suspension of Escherichia coli, which are known for their run and tumble motion. As a consequence, we find that the fluid flow generated by electric field, induces attractive hydrodynamic interaction between the swimming bacterial which in turn leads to bacterial clusters. Indicating that the applied electric force completely disrupted and drowns the self-generated hydrodynamics of swimming bacterial cells. Our results will allow us to examine the relative importance of fluid flow bacteria cell transport and other bacterial process
Keywords: Hydrodynamic interactions, Bacteria, Self-propelled, fluid flow